2019
DOI: 10.24953/turkjped.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Atypical phenotype of an old disease or typical phenotype of a new disease: deficiency of adenosine deaminase 2

Abstract: phenotype of an old disease or typical phenotype of a new disease: deficiency of adenosine deaminase 2. Turk J Pediatr 2019; 61: 413-417. Deficiency of adenosine deaminase 2 (DADA2) is an autosomal recessive autoinflammatory disorder caused by mutations in CECR1 (cat eye syndrome chromosome region, canditate 1) gene, which encodes the enzyme adenosine deaminase 2 necessary for endothelial cell survival and function. The diversity of the clinical phenotypes associated with DADA2 include polyarteritis nodosa-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Batu et al [16] case series, reported 1 patient with intestinal renal involvement from amyloidosis; also another one reported 1 patient treated with canakinumab for AA amyloidosis secondary to DADA2 with good outcomes [17]. Advances in sequencing technologies and international collaborations led to a better knowledge of mechanisms driving to autoinflammatory diseases, and many new disorders have been reported recently [1]. Initially, described in 2014, DADA2 is recognized as a mimic of PAN with primary features of early-onset strokes, peripheral vasculopathy, and systemic inflammation [2].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Batu et al [16] case series, reported 1 patient with intestinal renal involvement from amyloidosis; also another one reported 1 patient treated with canakinumab for AA amyloidosis secondary to DADA2 with good outcomes [17]. Advances in sequencing technologies and international collaborations led to a better knowledge of mechanisms driving to autoinflammatory diseases, and many new disorders have been reported recently [1]. Initially, described in 2014, DADA2 is recognized as a mimic of PAN with primary features of early-onset strokes, peripheral vasculopathy, and systemic inflammation [2].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in sequencing technologies and international collaborations led to a better knowledge of mechanisms driving to autoinflammatory diseases, and many new disorders have been reported recently [ 1 ]. Initially, described in 2014, DADA2 is recognized as a mimic of PAN with primary features of early-onset strokes, peripheral vasculopathy, and systemic inflammation [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations